Menghargai Kepustakaan Metafizik Islam: Merujuk Khusus al-Futuhat al-Makkiyyah Karya Ibn al-`Arabi (560H./1165M.-638H./1240M.) - Badron, Mohd Sani (Afkar: Jurnal Akidah dan Pemikiran Islam, 2008)
Great books on metaphysics (tasawwuf), such as the Futuhat Makkiyyah, in order to be duly appreciated, need to be studied in a proper manner. In this article, the status of the Futuhat amongst Ibn al-`Arabi’s various works will be clarified, emplacing it in the context of the author’s life. Exposition is offered on the epistemological basis of the Futuhat, as well as fundamentals of the worldview of Islam on Muslim general creeds of the testimony la ilaha illa Allah.